(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article analyzes the attitude of Soviet authorities towards the national art and traditions of the peoples of Turkestan following the revolution in the Russian Empire, its subsequent collapse, and the establishment of Soviet power in Turkestan. It examines the reforms implemented in the socio-political, spiritual, and cultural spheres, as well as the problems within the existing system.